Effectiveness of Artificial Intelligence in Enhancing Design User Experience Productivity - Nouf Nasser Alhazmi (International Journal of Computers and Informatics, 2025)
This study aims to identify and map the applications of Artificial Intelligence (AI) in the User Experience (UX) design process, exploring its potential to enhance efficiency, accuracy, and creativity in digital solutions. The analytical framework was developed based on a systematic literature review focusing on the stages of the User-Centered Design (UCD) process, in addition to a qualitative analysis of the impact of using ChatGPT on designers.The research also introduces the AI-Assisted Design (AIAD) methodology, which employs Deep Neural Networks (DNNs) to simulate user experience based on clickstream logs (e.g., page ID, coordinates, dwell time) to improve design accuracy and efficiency.The results reveal that AI is utilized across the different UCD stages, from understanding the context of use to developing solutions. Practitioners reported a notable increase in their perceived productivity, enabling them to accomplish more tasks in less time. However, the impact of AI on the sense of achievement is complex; while it enhances ownership and control through post-processing of AI outputs, it may also diminish due to reduced challenge or feelings of inferiority compared to machine-generated quality.AI proved particularly suitable for tasks such as understanding cognitive domains and generating creative solutions, yet less effective for in-depth research due to limited reliability. The study concludes that AI is not an all-powerful tool but rather a supportive assistant to designers. This work contributes to shaping the future research agenda toward a deeper understanding of human–AI collaboration in creativity and design.
Keywords: Artificial Intelligence (AI); User Experience (UX); User-Centered Design (UCD); Productivity; AI-Assisted Design (AIAD); Deep Neural Networks (DNN); ChatGPT; Human–AI Collaboration